2007
DOI: 10.1590/s0100-879x2007001100007
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism as a risk factor for cardiovascular disease in a Brazilian population

Abstract: TP53, a tumor suppressor gene, has a critical role in cell cycle, apoptosis and cell senescence and participates in many crucial physiological and pathological processes. Identification of TP53 polymorphism in older people and age-related diseases may provide an understanding of its physiology and pathophysiological role as well as risk factors for complex diseases. TP53 codon 72 (TP53:72) polymorphism was investigated in 383 individuals aged 66 to 97 years in a cohort from a Brazilian Elderly Longitudinal Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…In the gender comparison, SNP rs1042522 was associated with a significant risk of obesity in males when compared to females. These results are inconsistence with a previous study conducted in the Brazilian population, in which they reported that women conferred significant risk to develop obesity with SNP rs1042522 (Smith et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the gender comparison, SNP rs1042522 was associated with a significant risk of obesity in males when compared to females. These results are inconsistence with a previous study conducted in the Brazilian population, in which they reported that women conferred significant risk to develop obesity with SNP rs1042522 (Smith et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, p53 Arg72 genotype samples showed lower HDL levels when compared with other genotypes; a similar pattern was also reported in the European population (Smith et al 2007). The exact mechanism between a low level of HDL and p53 is not known, but this may lead to other health complications such as cardiovascular problems.…”
Section: Discussionsupporting
confidence: 91%
“…Our results corroborate a study conducted by Manfredi et al (2002) with 250 Italian individuals, which also did not find an association between the polymorphism of the p53 gene and AD. Smith et al (2007) analyzed 383 elderly patients with variants of AD and could not establish any association between this polymorphism and cardiovascular diseases. Alkhalaf et al (2007) found no association between codon 72 polymorphism of the p53 gene and CAD or diabetes in Kuwait individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association of dyslipidemia with p53 gene polymorphism and AD, Smith et al (2007) analyzed São Paulo (Brazil) population and found an association between the arginine allele and low levels of HDL cholesterol, which is considered a protective effect in the development of plaques of atherosclerosis. In the present study, this analysis was also performed, but we found no association.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studying the effect of Tp53 polymorphisms and their haplotypes on biochemical parameters revealed that codon 72 polymorphism in exon 4 significantly affect TG values. Compelling evidence suggests the fundamental role of p53 in adipose tissue metabolism and homeostasis, insulin resistance and development of metabolic diseases such as type 2 diabetes [ 40 ], cardiovascular diseases [ 41 ] and obesity [ 42 ]. A study on Brazilian population reported that Arg allele carriers showed lower HDL levels and a higher frequency of cardiovascular disease than Pro allele subjects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%